THROUGH THE MIRAGE: RETRACING MOMENTS OF A WAR “UP THERE” - Ian Liebenberg (Scientia Militaria, 2011)
Review articles allow books to speak, however subjective such articles may be. Reviewers, participants and observers share their reading of the written work or discourse as interpreted by human beings within time and context. If Anthony Giddens is correct that segmental interests lie deeply embedded in structures of signification and if Feuer is to the point in his argument “that in ideology words are measured for their fire-power, not the truth they hold”, then any attempt to make sense of what happened where, when and how and with what consequences during the Border War/Bush War and its outcomes in Angola will be no easy matter for historians and social scientists. It is understandable that for the observer and participant alike it seems that “truth” and “fact” became obscured by the drifting smoke and dust of past ideological and military struggles. Include the static views then held, and none closer do we come to understanding this war in all its complexity.